13y-6=2y+27

Simple and best practice solution for 13y-6=2y+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13y-6=2y+27 equation:



13y-6=2y+27
We move all terms to the left:
13y-6-(2y+27)=0
We get rid of parentheses
13y-2y-27-6=0
We add all the numbers together, and all the variables
11y-33=0
We move all terms containing y to the left, all other terms to the right
11y=33
y=33/11
y=3

See similar equations:

| 20x-2=18×+6 | | -1/3n+8=9 | | 2x+2+3x-17=180 | | 15-5x+7x=3x+15-x | | 26-x=7 | | 6x-25+3x-18+2x=180 | | 12x-18=5x+59=180 | | 600+x=1,932 | | 5x^2+8x=20 | | 15-5x+7x=3x+10-x | | -5a-27=4(2-3a) | | 66=n(n-1)/2 | | 2(1-x)+5=4-(x-3 | | 15-5x+6x=3x+15+2x | | 1/3(6x-9)+x=21 | | 3x-6=20+5(x-4) | | n2-14n+42=-6 | | 15-5x+7x=x+15-3x | | 4n-3=-2n-1 | | 6+18x=18x-18 | | 3x-5=x^2+5x-13 | | 8t-(6t-1)-2=5 | | 1x-11=-5 | | 1-v-v=v-5-2v | | 5x+8=-62-5xx= | | 6x-4=-9x | | 7+2x=x-(5-4x) | | 9+17x-6=7x+111-2x | | 4(n+6)=36 | | 3x(10x-15)=180 | | -2=(3x+11)/2 | | 7x+10=4-x |

Equations solver categories